Efeitos do treinamento físico aeróbio em ratos espontaneamente hipertensos sobre o balanço térmico e a expressão proteica de UCP1, UCP3 e BDNF - Helton Oliveira Campos (2017)
Thermoregulation occurs by the balance between the mechanisms of heat production and dissipation between the body and the environment. Spontaneously hypertensive rats (SHR) present an imbalance in the body temperature regulation during physical exercise because of several cardiovascular dysfunctions. The present study hypothesized that aerobic physical training would prevent the thermal imbalance presented by hypertensive animals during physical exercise. Thus, the aim was to verify the effects of aerobic physical training on the thermal balance and verify the possible changes in the mechanisms of production and heat loss in hypertensive rats. For this, Wistar normotensive rats (WNR) and SHR of 5 weeks of age at the start of the experimental protocol were used. The animals were randomly divided in 4 experimental groups: WNR untrained (WNR-NT), WNR trained (WNR-T), SHR untrained (SHR-NT) and SHR trained (SHR-T). The aerobic physical training program was carried out on a treadmill for 8 weeks, 5 days a week. Blood pressure and physical performance of the animals were measured before and after the physical training. After physical training protocol, the animals were submitted to a constant speed exercise until fatigue (60% of maximum speed), in which the following variables were analyzed: core body temperature, tail skin temperature, oxygen consumption and mechanical efficiency. Afterwards, animals were euthanized and the brown adipose tissue and the soleus and gastrocnemius muscles were removed. Protein expression of UCP1 (brown adipose tissue), UCP3 (soleus) and BDNF (soleus and gastrocnemius) were quantified by means of Western blot. Aerobic physical training prevented the thermal imbalance presented by hypertensive animals, once it attenuated exacerbated hyperthermia exercise-induced in untrained hypertensive. This response appears to be related to increased peripheral vasodilation, improved thermo-effector response, increased mechanical efficiency, reduced brown adipose tissue mass and increased BDNF expression. From the results achieved, it can be concluded that aerobic physical training corrects the thermal imbalance presented by hypertensive animals during exercise.